Acid switched efficient, cost effective, selective separation and determination of selenium(IV). Issue 5 (October 2017) - Barache, Umesh B.; Shaikh, Abdul B.; Lokhande, Tukaram N.; Anuse, Mansing A.; Kamble, Ganesh S.; Gurame, Vashishtha M.; Gaikwad, Shashikant H.
Graphical abstract: Highlights: CBIMMT shows outstanding sensing behavior with selenium(IV) in acidic medium. Selenium complex extracted in single step and exhibits λmax at 470 nm. No need of synergent, surfactant and heating for color development of complex. No need of any complicated instrumentation and tedious procedure. Reliable separation and quantification of Se(IV) from various samples. Abstract: The complexing reagent 4-(4′-chlorobenzylideneimino)-3-methyl-5-mercapto-1, 2, 4-triazole (CBIMMT) in dichloromethane forms orange colored complex with selenium(IV) and shows maximum absorption intensity at λmax 470 nm. The optimized conditions for complex formation and extraction were found to be, 7.0 mol L −1 HCl, 10 mL 0.06 mol L −1 CBIMMT in dichloromethane and 3 min equilibration time at room temperature. Under optimal conditions Beer's law and Ringbom's plot of the orange colored [Se(IV)-CBIMMT] complex in dichloromethane are obeyed in the concentration range of 15 to 50 μg mL −1 and 15 to 35 μg mL −1 of selenium(IV) ion respectively. The values of molar absorptivity and Sandell's sensitivity of the complex are 0.3341 × 10 4 L mol −1 cm −1 and 0.07092 μg cm −2 respectively. The stoichiometry of the [Se(IV)-CBIMMT] complex in dichloromethane is 1:1 determined by Job's method of continuous variation, molar ratio method and slope ratio method. Interference of large number of foreign ions is also studied and the selectivity of the current method was enhanced by using masking agents. Relative standard deviation (R.S.D.) (n = 5) was found to be 0.65% indicating the reproducibility of method. The method is successfully applied for determination of selenium(IV) from multicomponent ternary synthetic mixtures, water, biological, pharmaceutical samples and separation of selenium(IV) from related metals ions has also been studied with satisfactory results. This method has distinctive advantages such as selectivity and sensitivity, and it has been efficiently applied for determination of selenium (IV) from various samples within short time.